Evaluation of liver transplant recipients underwent incidental appendectomies - Cemalettin Koc; Sami Akbulut; Baris Sarici; Sezai Yilmaz (İstanbul Kuzey Klinikleri, 2020)
OBJECTIVE: To assess the clinicopathological features of liver transplant recipients underwent incidental appendectomies. METHODS: Between September 2002 and July 2019, 2500 patients underwent liver transplantation at our Liver Transplant Institute, including 38 (24 males, 14 females) who also underwent incidental appendectomies. Incidental appendectomies were performed on 24 patients during recipient hepatectomies and on 14 during relaparotomies due to various surgical conditions. The following patient parameters were retrospectively evaluated: age, sex, underlying liver disease, liver transplant type, appendectomy indication, appendix length (mm) and diameter (mm), presence of appendicitis, and histopathological findings. RESULTS: The 38 patients who underwent incidental appendectomies had a mean age of 18.3+-21.7 (range: 1–66) years and median appendix lengths and diameters of 55 (range: 19–90) mm and 6 (range: 4–20) mm, respectively. Histopathologically, the appendectomy specimens were classified as follows: vermiform appendix (n=16), lymphoid hyperplasia (n=13), acute appendicitis (n=3), fibrous obliteration (n=3), perforated appendicitis (n=1), mucinous cystadenoma (n=1), and appendiceal serosa invasion by sigmoid adenocarcinoma (n=1). There were no postoperative complications, including wound infections, abscesses, or leakage from the appendiceal stumps, related to the incidental appendectomies. CONCLUSION: This study demonstrated that incidental appendectomies can be successfully performed in immunosuppressed patients. However, additional studies are required to confirm these results.